A viable systems perspective to knowledge management - Yang, Chyan; Yen, Hsueh-Chuan (My University, 2007)
Purpose - To provide the knowledge structure for an effective knowledge-based organization which integrates knowledge into organizational goals. Design/methodology/approach - The structure, function, and process of a viable organization were discussed which provided a basis to construct a knowledge management (KM) framework and demonstrate knowledge structure in a knowledge-based organization. Based on systems view and viable systems model (VSM), a range of recently published KM practices were reviewed to position various knowledge content. Findings - This study proposed a viable systems framework for organizational KM based on the VSM of Beer. Using the viable systems framework, organizational knowledge can be classified into four categories. Knowledge content was articulated based on the systems view. Thus, knowledge structure of various management hierarchies can be captured. Originality/value - The result contributes to the practice of knowledge executive by supporting the diagnosis and design of an effective knowledge-based organization. The framework also provides a basis for future empirical studies on the relationships between KM strategies and organizational effectiveness. A specific KM strategy exists that can maximize the effectiveness of each of the four types of knowledge.
Keywords: knowledge management; organizations; systems analysis